2018
DOI: 10.1080/23273798.2018.1524500
|View full text |Cite
|
Sign up to set email alerts
|

Lexical prediction in language comprehension: a replication study of grammatical gender effects in Dutch

Abstract: An important question in predictive language processing is the extent to which prediction effects can reliably be measured on pre-nominal material (e.g. articles before nouns). Here, we present a large sample (N = 58) close replication of a study by Otten and van Berkum (2009). They report ERP modulations in relation to the predictability of nouns in sentences, measured on gendermarked Dutch articles. We used nearly identical materials, procedures, and data analysis steps. We fail to replicate the original eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 44 publications
4
46
2
Order By: Relevance
“…However, as in recent replication attempts (Nieuwland et al, 2018;Ito et al, 2017a;Kochari & Flecken, 2019;Kochari & Flecken, 2019), the patterns we found are in the expected direction in terms of polarity: the more unexpected the gender of the determiner, the larger the negativity of the average amplitude from the typical electrodes and time window of the N400 effect. It is therefore unclear from a qualitative literature review alone how strong the evidence is in favor (or against) pre-activation.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, as in recent replication attempts (Nieuwland et al, 2018;Ito et al, 2017a;Kochari & Flecken, 2019;Kochari & Flecken, 2019), the patterns we found are in the expected direction in terms of polarity: the more unexpected the gender of the determiner, the larger the negativity of the average amplitude from the typical electrodes and time window of the N400 effect. It is therefore unclear from a qualitative literature review alone how strong the evidence is in favor (or against) pre-activation.…”
Section: Discussionsupporting
confidence: 85%
“…However, Otten and Van Berkum (2009) detected a negativity for unpredictable determiners in comparison with predictable determiners with visual presentation, similarly to what was detected in Otten et al (2007) (with adjectives and auditory presentation). Kochari and Flecken (2019) attempted a replication of Otten and Van Berkum (2009) with a larger sample size ( = 70 vs. = 38), and while they failed to find a significant effect at the gender-marked determiner, they did observe a pattern consistent with the original experiment. Recently, Fleur, Flecken, Rommers, and Nieuwland (2019) manipulated gender expectancy and whether the expected noun phrase would be definite or not in Dutch, and detected an N400-like effect for the gender manipulation.…”
Section: Evidence For the Access Viewmentioning
confidence: 79%
See 2 more Smart Citations
“…First, the simulations provide a mechanistically explicit account of article induced N400 effects that does not depend on prediction at the level of word forms, but rather treats N400 amplitudes as the change in the conditional probabilities of semantic features cued by encountering the articles (Rabovsky et al, 2018;Rabovsky & McRae, 2014;Yan, Kuperberg, & Jaeger, 2017). This explanation differs from the most common interpretation of these effects Hagoort, 2017;Lau et al, 2008;Pickering & Garrod, 2013) and can, from the perspective implemented in the model, also be applied to related findings concerning article gender (see Kochari &Nicenboim et al, 2019 for recent reviews; see Fleur, Flecken, Rommers, & Nieuwland, 2019 for evidence consistent with the view that word form prediction may not be essential).…”
Section: Discussionmentioning
confidence: 95%